Upper-body haptic system for snake robot teleoperation in pipelines. (January 2022) - Zhu, Qi; Zhou, Tianyu; Du, Jing
Abstract: Snake robots have shown a great potential for operations in confined workplaces that are less accessible or dangerous to human workers, such as the in-pipe inspection. However, the snake robot teleoperation remains a nontrivial task due to the unique locomotion mechanism (e.g., helical motion) and the constraints of the workplaces including the low visibility and indistinguishable features. Most snake robot feedback systems are based on the live camera view only. It is hard for the human operator to develop a correct spatial understanding of the remote workplace, leading to problems such as disorientation and motion sickness in snake robot teleoperation. This study designs and evaluates an innovative haptic assistant system for snake robot teleoperation in the in-pipe inspection. An upper-body haptic suit with 40 vibrators on both the front and back sides of the human operator was developed to generate haptic feedback corresponding to the bottom and up sides of the snake robot, transferring the egocentric sensation of the snake robot to the human operator. A human-subject experiment (n = 31) was performed to evaluate the efficacy of the developed system. The results indicate that the proposed haptic assistant system outperformed other feedback systems in terms of both task performance and subjective workload and motion sickness evaluations. It inspires new control and feedback designs for the future snake robot in industrial operations.